Working Memory Deficits and its Relationship to Autism Spectrum Disorders - Rabiee, Atusa (Iran J Med Sci, 2020)
BACKGROUND: There is a wealth of research done in developed countries on the investigation of the working memory (WM) performance in people with high-functioning Autism Spectrum Disorders (ASD) (IQ>70), with different reported findings. There is a dearth of similar studies in developing countries. In addition, the findings suggest that WM is possibly influenced by culture. The present study investigated WM performance and its relationship with the symptoms of ASD and Attention Deficit Hyperactivity Disorder (ADHD). METHODS: The present study is a cross-sectional comparative study between two groups of participants with high-functioning ASD, aged 8-16 years (n=30) and typically developing (n=30). This study was conducted in 2016-2017 in Tehran (Iran). The Multivariate Analyses of Variance (MANOVA) was used to compare the between-group differences on WM tasks. In addition, Pearson’s correlation coefficient was used to examine the relationship between the ASD and ADHD symptoms with WM performance. The data were statistically analyzed using the Statistical Package for the Social Sciences (SPSS), version 16. RESULTS: It was found that in general, WM was impaired in the people with ASD. Unexpectedly, in the present study, two subscales of Social interaction and Stereotyped Behaviors of the Gilliam Autism Rating Scale-Second Edition showed a significant positive correlation respectively with a score of two WM tasks, i.e. Visual Digit Span and Digit Span Forward. CONCLUSION: These results showed that WM was impaired in individuals with ASD and that could have implications for intervention, but it is necessary that therapists be careful in choosing the appropriate tasks for intervention.